Generational Gap of Pakistani-American Muslims in Ayad Akhtar’s Homeland Elegies - Busyeiri, Muhammad Latif; Ruslianti, Atikah (Universitas Sebelas Maret, 2022)
Immigrants must adjust since they are fundamentally different from those around them and confront several difficulties. Due to their differences in appearance, culture, or beliefs, they frequently encounter discrimination from others. The problems that various immigrant generations confront also influence their attitudes and stances. This research aims to investigate the generational gap that exists between first generation and second generation Pakistani-American Muslims immigrants as portrayed in the novel Homeland Elegies by Ayad Akhtar. This research is descriptive analytical research using Said’s postcolonial theory of orientalism. The findings indicate that there is a generational gap between first- and second-generation immigrants as they encounter different challenges and adapt differently.